A rare cause of brachial plexopathy: hereditary neuralgic amyotrophy - Serin, Hepsen Mine (Turk Pediatri Ars, 2019)
Neuralgic amyotrophy is characterized by recurrent, painful, unilateral neuropathy involving mainly the upper brachial plexus followed by muscle weakness and muscle wasting. There are two forms: idiopathic and hereditary. Hereditary neuralgic amyotrophy is an autosomal dominant disease that is often linked to a mutation of SEPT9, a gene of the Septin family. The phenotypic spectrum of the disease may include hypotelorism, cleft palate, and other minor dysmorphisms. The age of onset is from infancy to adulthood. Hereditary neuralgic amyotrophy can be triggered by external stimuli such as infections, vaccinations, cold, stress, surgery, and strenuous exercise. Here, we report a six-year-old girl who was found to have mutation in the SEPT9 gene when she presented with recurrent attacks of painful brachial plexopathy following vaccinations, and was diagnosed as having hereditary neuralgic amyotrophy.